The neural basis of effective memory therapy in a patient with limbic encephalitis. Issue 11 (13th March 2009) - Berry, E; Hampshire, A; Rowe, J; Hodges, S; Kapur, N; Watson, P; Browne, G; Smyth, G; Wood, K; Owen, A M
Abstract : Background: An fMRI study is described in which a postencephalitic woman with amnesia used a wearable camera which takes photographs passively, without user intervention, to record and review recent autobiographical events. "SenseCam" generates hundreds of images which can subsequently be reviewed quickly or one by one. Results: Memory for a significant event was improved substantially when tested after 4.5 weeks, if the patient viewed SenseCam images of the event every 2 days for 3 weeks. In contrast, after only 3.5 weeks, her memory was at chance levels for a similarly significant event which was reviewed equally often, but using a written diary. During the fMRI scan, the patient viewed images of these two events, plus images of an unrehearsed event and images from a novel "control" event that she had never experienced. There was no difference in behavioural responses or in activation when the unrehearsed and novel conditions were compared. Relative to the written-rehearsed condition, successful recognition of the images in the SenseCam-rehearsed condition was associated with activation of frontal and posterior cortical regions associated with normal episodic memory. Conclusion: SenseCam images may provide powerful cues that trigger the recall and consolidation of stored but inaccessible memories.